The Tomb of Hamshira of Jam Fateh Khan at Makli Hill, Thatta, Sindh: History and Architecture - Durrani, Mukhtar Ali; Qazi, Muhammad Naeem; Jan, Zakirullah; Khan, Mir Muhammad; Mujeeb, Zil-e-Huma (Ancient Pakistan, 2021)
The tomb of hamshira (sister) of Jam Fateh Khan was constructed at the Makli Hill necropolis in AD 1465. Her name is shrouded in mystery, however, historical and epigraphic sources mention one hamshira of Jam Fateh Khan, who remained the ruler of Sindh from AD 1413 to 1428. This tomb marks the earliest construction of three-tiered building at the site. The historical and architectural significance of the monuments supported by epigraphic evidence. which is discussed at length here.